Incidence and risk factors of hearing loss in patients with Turner Syndrome - Huijia Lin; Xiaoya Wang; Shuang Qin; Fanglan Luo; Yingmei Cen; Gendie E. Lash; Li Li (Frontiers Media S.A., 2023)
BackgroundHearing loss (HL) is one of the main medical complications for Turner Syndrome (TS) patients, with an earlier presentation and higher incidence than normal women. However, the etiology of HL in TS is unclear. The aim of this study was to investigate the hearing status of TS patients in China and the influencing factors, so as to provide a theoretical basis for early intervention treatment for TS patients with HL.MethodsIn total 46 female patients aged 14-32 diagnosed with TS received tympanic membrane and audiological examinations, including pure tone audiometry and tympanometry. In addition, the effects of karyotype, sex hormone levels, thyroid function, insulin, blood lipids, bone mineral density, age and other factors on hearing levels were analyzed, and the possible risk factors associated with HL in TS patients were explored.ResultsIn 9 patients (19.6%) had HL, including 1 (2.2%) with mild conductive hearing loss, 5 (10.9%) with mild sensorineural hearing loss, 3 (6.5%) with moderate sensorineural hearing loss. TS is often associated with age-related mid-frequency and high-frequency HL, and the incidence of HL increases with age. Compared with other karyotypes, patients with 45, X haplotype have an increased risk of mid-frequency HL.ConclusionsTherefore, karyotype may be a predictor of hearing problems in TS.